THE PUPPETEER’S BODY DISCIPLINARY POWER IN MALANG’S MASK PUPPET PERFORMANCE - Wahyuningtyas, Tri (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The two focuses of this research include describing the formation of the puppeteers' episteme in Malang district and explaining the process of internalizing the experience and reasoning of the puppeteer who acts as a director as well as a person possessing high spiritual strength. Second, the body discipline power of the Malang masked puppeteer. This qualitative research used interview and observation data which were analyzed using Michel Foucault's post-structuralist theory approach. The results of the study performance that puppeteers of mask puppet performance in Malang district have a stronger disciplinary power orientation compared to other puppeteers. The power of knowledge of puppeteers is obtained through disciplining the body which is built from its existence socially and environmentally. The puppeteer of mask puppet performance has roles as a person who has spiritual power and as a director in organizing the mask puppet performance. The power of knowledge of the puppeteer produces the discourse of the puppeteer who has autonomy and power. Keywords: DISCIPLINARY POWER,BODY, PUPPETEER